Complementary and alternative medicine use in Australian children with acute respiratory tract infection - A cross-sectional survey of parents. (May 2020) - Lucas, S.; Kumar, Dr.S.; Leach, Dr.M.J; Phillips, Dr.A.C.
Abstract: Background: Acute respiratory tract infection (ARTI) is a prevalent condition associated with serious health and economic implications. A range of strategies is used to manage ARTI in children, including complementary and alternative medicines (CAM). There has been little investigation into this area, and this study aims to address this knowledge gap. Methods: Primary carers of children aged from 0 to 12 years that utilised CAM for ARTI were invited to participate in the online survey in 2019. Survey data were analysed descriptively. Results: The 246 surveyed parents specified the types of CAM frequently used to manage ARTI in their children were home-remedies. Reasons parents reported using CAM were personal-beliefs and positive past-experience with CAM practitioners. Information sources that parents consulted when decision-making were education, naturopaths, and journals. Conclusion: Parents utilised diverse interventions, with home-remedies dominating the choice. Parents were most likely well-informed. Notably, parents indicated a preference for an integrative healthcare approach. Highlights: Home remedies are popular with parents to manage for acute respiratory infections in children. Personal beliefs and past experiences drive decision-making when using complementary and alternative medicine in children. Media don't persuade decision-making of parents that use complementary and alternative medicine forespiratory infections. Parents desire an integrated health care system with biomedicine and complementary and alternative medicine.